Finance analytics in business : perspectives on enhancing efficiency and accuracy - Taneja, Sanjay; Kumar, Pawan; Sood, Kiran; Özen, Ercan; Grima, Simon (Emerald Publishing Limited, 2024)
Finance Analytics in Business brings together specialists around the world working in various disciplines to reflect on finance analytics in business. This crucial field gives different views of a company's financial data, and helps it gain knowledge to take action to improve financial performance. The chapters discuss the Time Series Analysis with ARIMA Model, ARIMA Modelling in R, Credit Risk Modelling, GARCH Modelling, GARCH Models Best for Asset Returns, Software for conducting event studies (Eventus, STATA, Matlab, Event Study Metrics, Event Study Tools), Developing insights on Descriptive Analysis, Predictive Analysis, Prescriptive Analysis, Forecasting Methods, Decision Analysis, Analytics tools used in Banking, Role of Business Intelligence, Machine learning, financial Modelling, and Artificial intelligence in finance. Emerald Studies in Finance, Insurance, And Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.
Keywords: Business enterprises -- Finance.; Finance -- Data processing.; Business & Economics -- Corporate Finance -- General.; Finance and the finance industry.; Corporate finance.; elektronické knihy; electronic books